The effect of head turn velocity on cross-coupled stimulation during centrifugation - Sheehan, Scott E.; Young, Laurence R.; Jarchow, Thomas (Journal of vestibular research, 2008)
Short-radius centrifugation (SRC) provides a practical means of producing artificial gravity for long duration space flights, though perceptual side-effects could limit its operational feasibility. Head turns (HT) during SRC, other than those about the centrifugation axis, produce Cross-Coupled Stimulation (CCS), perceived as a tumbling sensation. CCS can be nauseagenic, though adaptation can minimize this detrimental effect over time. The force environment of CCS suggests that the head turn velocity plays a role in determining the stimulus magnitude, though its degree has not been characterized. Twenty-three subjects performed right quadrant head turns of 8 different velocities while spinning at 19 and 23 RPMs on the SRC over two consecutive days. The perceptual effects were characterized by subjective metrics, investigating the acute differences between velocities as well as the chronic effects on adaptation. It was found that the perceived CCS magnitude can be regulated by modulating HT velocity. Further, a threshold of HT velocity exists above which an asymptotic perceptual response is observed, and below which the perceptual response diminishes at an exponential rate relative to head turn velocity. Finally, the effects of HT velocity are independent of HT direction, though the differing head turn directions likely produce contextually specific stimuli. These results suggest that HT velocity modulation could provide a practical means of incremental adaptation to CCS during SRC.